A case of successful bystander cardiopulmonary resuscitation of an adult with Bland‐White‐Garland syndrome. Issue 11 (20th September 2017) - Fukuoka, Hidetada; Watanabe, Tetsuya; Shinoda, Yukinori; Ikeoka, Kuniyasu; Minamisaka, Tomoko; Inui, Hirooki; Ueno, Keisuke; Inoue, Soki; Mine, Kentaro; Toda, Koichi; Sawa, Yoshiki; Hoshida, Shiro
Key Clinical Message: In Japan and worldwide, the increase in educational interventions about resuscitation training significantly increases favorable neurological survival in out‐of‐hospital cardiopulmonary arrest cases treated with bystander cardiopulmonary resuscitation (BCPR) each year. This case with Bland‐White‐Garland syndrome having high‐quality BCPR by nurses demonstrates the importance of education about BCPR. Abstract : In Japan and worldwide, the increase in educational interventions about resuscitation training significantly increases favorable neurological survival in out‐of‐hospital cardiopulmonary arrest cases treated with bystander cardiopulmonary resuscitation (BCPR) each year. This case with Bland‐White‐Garland syndrome having high‐quality BCPR by nurses demonstrates the importance of education about BCPR.